2010
DOI: 10.1016/j.ijrobp.2009.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability Predicts Clinical Outcome in Radiation-Treated Endometrioid Endometrial Cancer

Abstract: Purpose-Microsatellite instability (MSI) is the hallmark of cancer with DNA mismatch repair (MMR) deficiency and underlies 20-30% of endometrial cancer. Some in vitro studies suggest that radiation effects are modulated by the MMR system, however, little is known about the relationship between MSI and radiation response. The aim of this study was to elucidate whether MSI predicts clinical outcome in radiation treated endometrioid endometrial cancer (EEC).Methods-We have studied a consecutive series of 93 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
3
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 15 publications
5
33
3
14
Order By: Relevance
“…The study concluded on a negative prognostic value of MSI-H cases, but in contrast to our study all of their cases were radiation-treated [6]. MSI-L and MSI-H were found in 11% and 16% of the cancers analyzed (totalling 27%).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The study concluded on a negative prognostic value of MSI-H cases, but in contrast to our study all of their cases were radiation-treated [6]. MSI-L and MSI-H were found in 11% and 16% of the cancers analyzed (totalling 27%).…”
Section: Discussioncontrasting
confidence: 94%
“…Another shortcoming was that the MSI markers used were less sensitive than the recently described ones assessed by the pentaplex polymerase chain reaction assay [8,9,42]. Another recent study of interest investigated early stage radiation-treated endometrioid tumors only with the same MSI markers as ours, and concluded on a negative prognostic value for MSI-H patients [6].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…MMR genes may be abnormally methylated and cancer develops when MSI occurs in regions of tumor suppressor genes. Numerous microsatellites are detectable by PCR and are found in 20-40% of cases of endometrial cancer (22,(55)(56)(57). Genes involved in the MMR system include hMLH1, MutS protein homolog 2 (hMSH2) and hMSH6, and postmeiotic segregation increased 2 (hPMS2) is frequently abnormally methylated (56).…”
Section: Diagnosis Of Endometrial Cancer and Epigenetic Abnormalitiesmentioning
confidence: 99%
“…Numerous microsatellites are detectable by PCR and are found in 20-40% of cases of endometrial cancer (22,(55)(56)(57). Genes involved in the MMR system include hMLH1, MutS protein homolog 2 (hMSH2) and hMSH6, and postmeiotic segregation increased 2 (hPMS2) is frequently abnormally methylated (56). hMLH1 methylation has been found in 40.1% of cases of endometrial cancer and in 14.3% of cases of atypical endometrial hyperplasia, a precancerous endometrial lesion; therefore, abnormal methylation of hMLH1 is considered to be significantly involved in carcinogenesis (43).…”
Section: Diagnosis Of Endometrial Cancer and Epigenetic Abnormalitiesmentioning
confidence: 99%